Limbah Fermentasi Kombucha Bunga Telang Sebagai Produk Bioteknologi Berupa Pupuk Cair Organik Dalam Menunjang Pertumbuhan Seledri - Rezaldi, Firman; Kartina, Kartina; Susiyanti, Susiyanti; Maritha, Vevi; Susilo, Hadi (Jurnal Ilmiah Biosaintropis (Bioscience-Tropic), 2024)
Fertilizers produced from a mixture of materials that are easily decomposed, easily improve the physical, chemical and biological properties of the soil because they contain nutrients as an effort to increase plant growth are known as organic liquid fertilizers. The purpose of this study was to determine the potential of organic liquid fertilizer derived from the waste of butterfly pea kombucha fermentation combined with EM4 on the growth of celery plants. The research design includes T1, namely without treatment. T2 is the waste of butterfly pea flower kombucha fermentation added with 1 mL/L of EM4. T3 is the waste of butterfly pea flower kombucha fermentation added with 3 mL/L of EM4. T4 is the waste of butterfly pea flower kombucha fermentation added with 5 mL/L of EM4. The parameters of this study include plant height and number of leaves. The results of this study proved that kombucha fermented telang flower waste combined with EM4 correlated positively in supporting the growth parameters of celery plants, both plant height and number of celery plant leaves. The conclusion from this research is that the 5 mL/L treatment of 5 mL/L kombucha fermentation waste is the best treatment to support the research parameters, namely growth data on the average plant height and the number of leaves of celery plants.